Collagen Density Regulates Tumour Spheroid Growth Through Cell Motility: A Computational Study - Godinho Gonçalves, Inês; García-Aznar, Jose Manuel (Jornada de Jóvenes Investigadores del I3A, 2021)
We aim to define the role of matrix density on tumour growth through a discrete computational framework. We integrate experimental data to characterize the dynamics of individual cellular movement, accounting for the mechanical properties of the ECM, and we evaluate how the emerging trends modulate the growth of multicellular structures.